The Un-bodied Voices in Shelley’s “To a Skylark” and Keats’s “Ode to a Nightingale” - Khadka, Kul Bahadur (Journal of Development Review, 2023)
B. Shelley and John Keats are noted Romantic poets and their works are celebrated. In this article, Percy Bysshe Shelly’s “To a Skylark” and John Keats’s “Ode to a Nightingale” have been appreciated. The skylark and the nightingale seem to be similar birds while reading the poems simultaneously. Shelley glorifies the skylark’s song and Keats immortalizes the nightingale due to its melodious song. The article, structured in four headings- Introduction, Appreciating, The Un-bodied Voices and Conclusion, introduces the poets and their aforesaid poems. It appreciates both the poems in matter of the contrasts and commonalties between the birds, the major themes in the poems, the poets’ power of imagination and the un-bodied voices in the poems. It makes a quest for how the un-bodied voices in the poems represent idealism in contrast to the harsh reality of life. To appreciate the poems and further strengthen the ideas, the poets’ respective poems and books by various writers have been consulted. The article concludes that the songs of the skylark and the nightingale are the un-bodied voices which symbolize beauty, purity, perfection and freedom. These un-bodied voices are in contrast to the harsh reality of human life on the earth.